Pemberdayaan Masyarakat di Kelompok Tani Ternak “Batu Kalang Indah” sebagai Upaya Peningkatan Populasi Ternak Sapi di Nagari Ampang Pulai - Tinda Afriani; Teguh Prasetyo; Wahyuni Eloisa Miranda; Nelwitis Nelwitis (Warta Pengabdian Andalas, 2021)
The “Batu Kalang Indah” Livestock Farmers Group, which was chosen as a partner in the community service activity proposal, is located in Ampang Pulai sub-district, XI Koto Tarusan District, Pesisir Selatan Regency. The distance of the Assisted Cattle Group from the UNAND Faculty of Animal Husbandry is around <200 km. This group still has an average number of services per conception (S/C) of nearly 2, most of the parents showed two artificial inseminations (AI) just became pregnant. Besides the high S/C value, post partum estrus (PPE) is also long, some for more than one year. Feeding conditions also experience problems in this group, meanwhile the lust conditions of the cows that are not known to breeders are also a problem. The benefit of this service activity is to increase the parent population that is kept by breeders in this group, with the hope of increasing the income and welfare of the breeders. Activities that will be carried out are assistance in raising beef cattle, processing rice straw-based feed and procuring bulls as lust biostimulation and implementing scheduled IB. This activity is carried out by methods of preparation, counseling and training, guidance and coaching, discussion and consultation, implementation of community service and evaluation and monitoring. The result of this activity is that breeders have known the proper and measurable ways and patterns of raising cattle. It is hoped that this activity can provide information related to maintenance patterns that can be applied sustainably to this livestock group.